Numerical Constraints on Folding and Thrusting in Jiudong Basin: Implication for the Northeastward Growth of Qinghai–Tibetan Plateau - Chen, Qizhi; Hu, Caibo; Orellana-Rovirosa, Felipe; Zhou, Longshou; Zhang, Huai; Shi, Yaolin (Frontiers in Earth Science, 2022)
Under regional tectonic shortening in the northern margin of Qinghai-Tibetan Plateau, the fold-and-thrust belts composed of four thrust faults (North Qilian-Shan, North Yumu-Shan, South Heli-Shan, and North Jintanan-Shan) formed from southwest to northeast discontinuously-sequentially in Jiudong Basin area during Late Cenozoic. Meanwhile the North Qilian-Shan, Yumu-Shan and Heli-Shan ranges were formed successively as the Earth's local surface was unequally uplifted. In this study, based on geological and geophysical observations, a simple two-dimensional elasto-plastic numerical FEM model for a southwest-northeast section in Jiudong Basin is successfully established to simulate the spatio-temporal evolution of the local fold-and-thrust belts. Results show that the computed equivalent-plastic-strain concentration zones and the four observed thrust-faults are consistently-correlated in spatial position-orientation and time sequence. The simulated upper-surface deformation is congruent with the observed topographic-peaks and uplift sequences of North Qilian-Shan, Yumu-Shan, and Heli-Shan ranges. This study provides geodynamic basis for understanding the growth mechanism of the northern margin of Qinghai–Tibetan Plateau under tectonic horizontal shortening. Also, we provide a thorough sensitivity analysis for the model parameters of this particular geological setting. Our sensitivity simulations considering systematic case variations about the regional geometrical-material parameters, suggest the manifestation of three different possible evolution patterns of fold-and-thrust belts for a wedge above a decollement layer; with wedge plastic deformation migrating from: (1) thick to thin end (well-known), (2) thin to thick end, and (3) both ends to middle. Finally, our results suggest that in this region further growth of mountain ranges is expected to continue in the future.